Black soldier fly larvae oil: A functional lipid that improves insulin sensitivity mainly by inhibiting the PPAR and MAPK signaling - Jie Peng; Xichen Zhao; Yimei Tang; Ziying Li; Yanle He; Qiwen Huang; Guohua Tan; Wuhao Chen; Shuangyan Mo; Guoxia Wang; Wei Wang; Yanhua Huang (Future Foods)
Black soldier fly larvae (BSFL) contains various functional components such as larva oil, but their nutritional efficacy still have not been well defined. Hence, we explored the effects of BSFL oil (10.0 %) on maternal and their progeny health in a mouse model. The results showed that BSFL oil intake had no effect on the fetuses development but had improved the colonic morphology in the mice during the gestation. Besides, the maternal glucose tolerance was improved. During the lactation period, BSFL oil intake obstructed the increasement in body weight induced by high-fat-diet (HFD). In addition, BSFL oil can alleviate HFD-induced increase in serum lipids and oxidative stress in 21.5 d and 10 weeks offspring. Utilizing RNA sequencing (RNA-seq) and immuno-histochemical analysis, we conclusively demonstrated that BSFL oil possesses the capacity to enhance insulin sensitivity and mitigate oxidative stress in the body, primarily through the suppression of the peroxisome proliferators activated receptor (PPAR) and mitogen activated protein kinase (MAPK) signaling cascades.